The End of the West : the Once and Future Europe - Marquand, David (Public square (Princeton, N.J.), 2012)
Has Europe's extraordinary postwar recovery limped to an end? It would seem so. The United Kingdom, Belgium, France, Italy, and former Soviet Bloc countries have experienced ethnic or religious disturbances, sometimes violent. Greece, Ireland, and Spain are menaced by financial crises. And the euro is in trouble. In The End of the West, David Marquand, a former member of the British Parliament, argues that Europe's problems stem from outdated perceptions of global power, and calls for a drastic change in European governance to halt the continent's slide into irrelevance. Taking a searching loo.